A Comparative Analysis of Conventional and Hybrid Simulation in Tropical Hotel Energy Modeling - Young, Hepi Duchovny; Setyowati , Erni; Prianto, Eddy; Dwiyanto, Agung (ASTONJADRO, 2026)
The hospitality industry in tropical climates faces significant challenges in managing energy use while trying to make buildings that are environmentally friendly in areas with high temperatures, humidity, and changing weather.  Hotels in places like Southeast Asia, the Caribbean, and sub-Saharan Africa usually use a lot of energy each year. This is mainly because they need heating, cooling, and lighting, which raises costs and harms the environment.  As tourism increases and climate change becomes more of a problem, energy-efficient hotel designs and sustainability metrics have become more critical in international policy frameworks. This systematic literature review assesses the efficacy of hybrid simulation methodologies, combining various modeling tools to evaluate climatic impacts on enhancing energy efficiency and sustainability in tropical hotels, in contrast to conventional standalone simulations.  Using a strict PRISMA-guided method, searches of databases found 95 records, which led to one relevant observational modeling study of medium-category Mexican hotels.  This study showed a statistically significant drop in CO2 emissions and energy use per room-year, with older guests seeing the most benefits. The review shows that hybrid simulation has a lot of potential to improve hotel energy systems and make operations more sustainable, even though the sample size is small, the data is simulated, and there is no meta-analysis.  Practical implications encompass the endorsement of pilot implementations, personnel training, and collaborations to mitigate financial obstacles.  The review also points out significant research gaps, like a lack of long-term data and a lack of representation for tropical regions. This shows that more empirical research is needed. In general, using hybrid simulation methods could make hotels in tropical climates more energy-efficient and better able to handle environmental changes, which would help the hospitality industry become more sustainable.